Coronavirus Disease 2019 in Solid Organ Transplant: A Multicenter Cohort Study. (7th August 2020) - Kates, Olivia S; Haydel, Brandy M; Florman, Sander S; Rana, Meenakshi M; Chaudhry, Zohra S; Ramesh, Mayur S; Safa, Kassem; Kotton, Camille Nelson; Blumberg, Emily A; Besharatian, Behdad D; Tanna, Sajal D; Ison, Michael G; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has led to significant reductions in transplantation, motivated in part by concerns of disproportionately more severe disease among solid organ transplant (SOT) recipients. However, clinical features, outcomes, and predictors of mortality in SOT recipients are not well described. Methods: We performed a multicenter cohort study of SOT recipients with laboratory-confirmed COVID-19. Data were collected using standardized intake and 28-day follow-up electronic case report forms. Multivariable logistic regression was used to identify risk factors for the primary endpoint, 28-day mortality, among hospitalized patients. Results: Four hundred eighty-two SOT recipients from >50 transplant centers were included: 318 (66%) kidney or kidney/pancreas, 73 (15.1%) liver, 57 (11.8%) heart, and 30 (6.2%) lung. Median age was 58 (interquartile range [IQR] 46–57), median time post-transplant was 5 years (IQR 2–10), 61% were male, and 92% had ≥1 underlying comorbidity. Among those hospitalized (376 [78%]), 117 (31%) required mechanical ventilation, and 77 (20.5%) died by 28 days after diagnosis. Specific underlying comorbidities (age >65 [adjusted odds ratio [aOR] 3.0, 95% confidence interval [CI] 1.7–5.5, P  < .001], congestive heart failure [aOR 3.2, 95% CI 1.4–7.0, P  = .004], chronic lung disease [aOR 2.5, 95% CI 1.2–5.2, P  = .018], obesity [aOR 1.9, 95% CI 1.0–3.4, P  = .039]) and presenting findings (lymphopenia [aOR 1.9, 95% CI 1.1–3.5, P  = .033], abnormal chest imaging [aOR 2.9, 95% CI 1.1–7.5, P  = .027]) were independently associated with mortality. Multiple measures of immunosuppression intensity were not associated with mortality. Conclusions: Mortality among SOT recipients hospitalized for COVID-19 was 20.5%. Age and underlying comorbidities rather than immunosuppression intensity-related measures were major drivers of mortality. Abstract : In this analysis of 482 solid organ transplant recipients with coronavirus disease 2019 (COVID-19), the authors report 28-day mortality of 20.5% among inpatients, strongly associated with age and comorbidities, and conclude that this is comparable to rates observed in the general population.